Characteristics of Femoral Torsion Angles and Relationships Between Femoral Torsion Angles and Hip Rotational Motion Variables in Adult Baseball Players - Takeuchi, Satoshi (Orthop J Sports Med, 2020)
BACKGROUND: Abnormalities in hip rotational motion (HRM) are risk factors for throwing injuries. To evaluate hip rotational motion, it is necessary to assess the torsion angle. However, no studies have investigated the femoral torsion angle (FTA) in baseball players. PURPOSE: To investigate differences in hip FTA of adult baseball players through use of ultrasonography to evaluate the relationship between the FTA and HRM. STUDY DESIGN: Cross-sectional study; Level of evidence, 3. METHODS: A total of 149 elite male baseball players (mean age, 20.0 ± 1.8 years; 64 pitchers, 85 position players) were enrolled in this study. Ultrasonographic assessment of FTA was performed based on the tilting angles of the anterior surface of the femoral neck and condylar axis. The hip internal rotation (HIR) and hip external rotation (HER) were assessed at 0° and 90° of flexion. Data related to FTA and HRM were compared between hips and between pitchers and position players. RESULTS: No significant difference was observed in the FTAs between hips for any player (lead hip, 20.5° ± 9.2°; trail hip, 19.6° ± 9.8°; P = .276). No significant difference was observed in FTAs of both hips between pitchers and position players (lead hip, 20.1° ± 9.4° and 20.9° ± 9.0°, respectively, P = .957; trail hip, 19.5° ± 9.8° and 19.7° ± 9.8°, P = .999). In terms of HER in 90° of hip flexion in both hips, significant differences were observed in HRM variables between pitchers and position players (lead hip, 33.0° ± 8.9° and 37.5° ± 9.8°, respectively, P = .024; trail hip, 35.6° ± 9.6° and 40.4° ± 10.2°, P = .035). Linear regression analysis revealed a significant agreement between the FTA and HIR at both 0° (R = 0.298, P < .001) and 90° of hip flexion (R = 0.279, P < .001). CONCLUSION: Our findings indicated that FTAs were not different between the hips of elite baseball players. Abnormalities of the HRM are not caused by differences in the FTA but rather involve soft tissue tightness around the hip area or other bony morphologic factors in the hip joint.